Simple, Fast, and Efficient Method for Derivation of Dermal Fibroblasts From Skin Biopsies. Issue 3 (13th March 2023) - Iannello, Grazia; Patel, Achchhe; Sirabella, Dario; Diaz, Alejandro Garcia; Hoover, Benjamin N.; Sarmah, Hemanta; Corneo, Barbara
Abstract: Primary fibroblasts are a precious resource in the field of translational regenerative medicine. Dermal fibroblasts derived from human subject biopsies are being used as donor tissues for the derivation of patient‐specific iPSC lines, which in turn are used for disease modeling, drug screening, tissue engineering, and cell transplantation. We developed a fast and simple protocol to grow dermal fibroblasts from skin biopsies. Using this protocol, we simply and firmly fix the biopsy piece on the surface of a tissue culture–treated plate and allow the fibroblasts to grow. This novel method eliminates any need for enzymatic digestion or mechanical dissociation of the biopsy piece. By using this newly developed protocol, we have successfully established around 100 fibroblast lines characterized by the expression of specific markers [Serpin H1 (Hsp‐47), F‐actin, and Vimentin]. Finally, we have used many of these fibroblast lines as donor tissues to successfully derive iPSC lines. We have developed a method that is simple, fast, convenient, efficient, and gentle on the cells to derive dermal fibroblasts from human skin biopsies. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Skin biopsy collection and fibroblast derivation Support Protocol 1 : Culturing, freezing, and thawing dermal fibroblasts derived from a skin biopsy Support Protocol 2 : Characterization of dermal fibroblasts by immunocytochemistry